ELECTRODYNAMICS CALCULATION OF LINEAR PAA WITH MATCHING PERIODICAL STRUCTURE - Маrchenko S. V.; Mоrоzоv V. М. (Radio Electronics, Computer Science, Control, 2013)
Matching of PAA with external space is an important problem. There are various methods of improvement of matching by usage of magnito-dielectric inserts and layers, diaphragms [1], inductive irises, impedance flanges [2], etc. In this work use of the matching device in the matching periodical structure (MPS) is considered. The MPS represents a subarray with the same cross sizes as the main antenna array ones, being at a certain distance over the main antennas. Calculation is carried out with integral equation method based on splitting of penetrating area. Numerical research of matching of PAA with external space showed that MPS improve matching at defined sizes and its arrangement. The parameters of MPS providing matching were numerically determined. On average the reflection coefficient when using MPS decreases by 3–4 times in the range of angles of scan from 0° to 60°.